Avaliação das águas superficiais do Rio Paraguai no trecho de Cáceres (MT) pelo teste de micronúcleos em peixes e teste mancha de asas de Drosophila - Pimenta, Vânia Maria Sartini Dutra (2008)
CHAPTER II: The genotoxic activity of surface water samples from four sites along the Paraguay River, near Cáceres, Mato Grosso State, Brazil, was investigated using the Drosophila melanogaster Somatic Mutation and Recombination Test (SMART). Effluents from sanitary sewers and agroindustrial effluents (residual effluents from slaughterhouses, leather tanneries, and dairies) flow into the Paraguay River, and directly or indirectly contaminate water from sampling Sites 1-3; Site 4 was an upriver reference site that received no domestic or agroindustrial discharges. Water was collected at 4 time periods, September 2003 and August 2004 (periods of low water or drought), and April 2004 and March 2005 (periods of high water or flood). Chromium concentrations above statutory limits were detected at Sites 1-3 (August 2004), and Sites 1, 2 and 4 (March 2005). Sulfur compounds were also detected for Sites 1-3. The SMART performed using standard (ST) cross flies detected genotoxic responses in only two samples, the August 2004 Site 1 sample and the March 2005 Site 2 sample. Many more samples were positive using high bioactivation (HB) cross flies: Site 1 (all collection periods), Site 2 (September 2003 and April 2004), and Site 3 (September 2003 and August 2004). Mutant frequency comparisons between marker-heterozygous and balancer-heterozygous flies from the HB cross indicated that the positive genotoxic responses for the Site 2 (April 2004) and Site 3 (September 2003) samples were due mainly to mitotic recombination. Our findings indicate that the section of the Paraguay River within the urban perimeter of Cáceres is contaminated with genotoxic agents. CHAPTER III: The quality of the water of the Paraguay River where it flows through the town of Cáceres, situated on the left margin of the river 210 km from Cuiabá, the capital of the state of Mato Grosso, Brazil, was evaluated based on the Micronucleus Test in Fish (MNTF) and chemical analyses. The main tributary of the Upper Paraguay Basin, the Paraguay River originates in the Planalto dos Parecis highlands in Mato Grosso and flows southeast through the Pantanal wetlands. The water in the stretch of the river under study is affected directly or indirectly by various anthropogenic actions. In April and August 2004, in the rainy and dry seasons, respectively, peripheral blood samples were collected from fish colleted at testing sites receiving: 1) upstream of the urban perimeter, used as reference. 2) the Sangradouro Stream (urban perimeter, sanitary sewage); 3) tannery discharge (from a large plant); Site 3 was downstream of the urban perimeter. Pimelodus maculatus (mandi) were collected at testing sites 1, 2, and 3 in both rainy and dry seasons, while Leporinus friderici (piau) was collected in the dry season only in testing sites 1 and 3. The river water and sediments were analyzed to determine sulfides, suspended solids, chromium (Cr), oils and fats, biochemical demand of oxygen, chemical demand of oxygen and sedimented solids. The results indicated that all the sites contained Cr, and that the sulfide content at sites 2 and 3, oils and greases exceeded the legal limit. The data showed a statistically significant increase in micronucleus (MN) frequencies in P. maculatus red blood cells at sites 2 and 3 compared with site 1, as well as statistically significant increases in the MN frequencies in L. friderici red blood cells at site 3 compared with site 1. Therefore, the results indicated significant increases in the rainy and dry season, demonstrating that the waters of the Paraguay River, as they flow through Cáceres, receive genotoxic effluents which may be associated with the presence of heavy metals (Cr), sulfates (S), oils or grease other chemical substances.